Answer:
either x or y must equal 0
Step-by-step explanation:
ts given that xy = 0
Remember that product of two numbers can be zero only if:
Both of them are zero or Either of them is zero as zero multiplied to any non-zero number will always be equal to zero. This is known as Zero Product Property.
So, if the product of x and y is equal to 0 there are two possibilities:
Both x and y are equal to 0
Either x or y must be equal to 0
Note that the condition both x and y are equal to zero is not a must condition, because even if one of them is equal to zero, the entire expression will be equal to zero.
Hence, the condition which has to be true in all cases for xy = 0 is:
either x or y must equal 0
1,009.479 just add themmmm
Answer:
The graph is not a line of best fit as there are not an equal number of data points on each side of the line
Step-by-step explanation:
Brainliest would be appreciated
Answer:
The <em>required probability</em> is .
Step-by-step explanation:
Let <em>A </em>be the event of rolling the number cube.
Let <em>B</em> be the event of tossing the coin.
Total number of possibilities of rolling the number cube and tossing the coin are <em>12 </em>here.
where <em>H</em> means Head on toss of coin and <em>T</em> means Tails on toss of coin.
Formula for probability of an event <em>E</em> is:
Here, we have to find the probability of event 'E' i.e. getting a 6 on number cube and heads on coin.
Number of favorable cases are <em>1 </em>and total cases are <em>12</em>.
Answer:
{x=2,y=2
Step-by-step explanation:
Equation 1:
Multiply both sides of the equation by a coefficient
{ 4(2x-y)=2*4
-5x+4y=-2
Apply Multiplicative Distribution Law
{8x-4y=2*4,-5x+4y=-2
8x-4y+(-5x+4y)=8+(-2)
Remove parentheses
8x-4y-5x+4y=8-2
Cancel one variable
8x-5x=8-2
Combine like terms
3x=8-2
Calculate the sum or difference
3x=6
Divide both sides of the equation by the coefficient of the variable
x=6/3
Calculate the product or quotient
x=2
Equation two:
{-5+4y=-2, x=2
-5*2+4y=-2
Calculate the product or quotient
-10+4y =-2
Reduce the greatest common factor (GCF) on both sides of the equation
-5+2y=-1
Rearrange unknown terms to the left side of the equation
2y=-1+5
Calculate the sum or difference
2y=4
Divide both sides of the equation by the coefficient of the variable
y=4/2
y=2
Hope this helps!!